Operational intervention levels for reactor emergencies IAEA recommendations (Brazilian Journal of Radiation Sciences, 2018)
The IAEA publication EPR-NPP-OILs-2017, OPERATIONAL INTERVENTION LEVELS FOR REACTOR EMERGENCIES AND METHODOLOGY FOR THEIR DERIVATION [1], provides selected default OIL values, describing a methodology for their derivation, as well as practical tools and recommendations for their use. IAEA recommends that tools and default OIL values be directly integrated into national emergency arrangements or reviewed and modified as necessary to meet the specific emergency preparedness and response arrangements. The Institute of Radiation Protection and Dosimetry (IRD) has a Radiological Assessment TEAM (EAR) as part of its Radiation Emergency Response System. Brazilian regulatory standards address actions for radiation emergencies encompassing necessary measures to assess public exposures, intervention levels to protect the public and recommendations for protective actions as, evacuation, relocation, sheltering and food restrictions. The objective of this paper is to present a discussion the use  these OILs, to compare those ones established by the Brazilian standards and to propose a methodology on  how OILs can be used by EAR/IRD  in case of an emergency at the Brazilian NPP.